2020
DOI: 10.1038/s41537-020-00129-w
|View full text |Cite
|
Sign up to set email alerts
|

General psychopathology links burden of recent life events and psychotic symptoms in a network approach

Abstract: Recent life events have been implicated in the onset and progression of psychosis. However, psychological processes that account for the association are yet to be fully understood. Using a network approach, we aimed to identify pathways linking recent life events and symptoms observed in psychosis. Based on previous literature, we hypothesized that general symptoms would mediate between recent life events and psychotic symptoms. We analyzed baseline data of patients at clinical high risk for psychosis and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…This is highly interesting, considering that already during the first timepoint nearly 10% of the responders indicated a subjective increase of schizotypy. Recent work shows the impact of adverse life events or loneliness on developing psychotic-like experiences ( Beards et al, 2013 ; Chau et al, 2019 ; Le et al, 2019 ; Betz et al, 2020 ). The social and life-changing consequences of this pandemic (i.e., general reduction of social interaction, job insecurity, experiencing health problems) might therefore provide a long-term risk of schizotypal trait exacerbation in those individuals with high schizotypy scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is highly interesting, considering that already during the first timepoint nearly 10% of the responders indicated a subjective increase of schizotypy. Recent work shows the impact of adverse life events or loneliness on developing psychotic-like experiences ( Beards et al, 2013 ; Chau et al, 2019 ; Le et al, 2019 ; Betz et al, 2020 ). The social and life-changing consequences of this pandemic (i.e., general reduction of social interaction, job insecurity, experiencing health problems) might therefore provide a long-term risk of schizotypal trait exacerbation in those individuals with high schizotypy scores.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent review by Preti et al (2020) the current pandemic poses an especially large risk for people suffering from paranoid or high schizotypal traits, as the measures taken to prevent the spread of the virus might ultimately lead to increased anxiety and depressive symptoms, increased avoidance behaviors, stronger disruption of social contacts, and delayed return to normality in these individuals. Furthermore, studies show links between recent adverse life events ( Beards et al, 2013 ; Betz et al, 2020 ) or isolation and loneliness ( Chau et al, 2019 ; Le et al, 2019 ) and schizotypy or psychosis-like experiences. Both these aspects, loneliness and adverse life events, are present in the current pandemic, which might have a worsening effect on schizotypal trait expression in people with pre-existing high schizotypy scores, perhaps leading to increased distress or disability.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we found that schizotypy scores stayed the same or even increased, which is highly interesting, considering that already during the first timepoint nearly 10% of the responders indicated a subjective increase of symptoms. Recent work shows the impact of adverse life events or loneliness on developing psychotic-like experiences (Beards et al, 2013; Chau et al, 2019; Le et al, 2019; Betz et al, 2020). The social and life-changing consequences of this pandemic (i.e., general reduction of social interaction, job insecurity, experiencing health problems) might therefore provide a long-term risk in those individuals with high schizotypy scores.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 13, 2021. ; https://doi.org/10.1101/2021.05.06.21256748 doi: medRxiv preprint Specifically, our results highlight how associations between affective and psychotic experiences may be differentially expressed in women and men. Following the theory of an affective pathway to psychosis, affective alterations, in particular depression and anxiety, may be fundamental driving forces of psychotic experiences (Betz et al, 2020;Isvoranu et al, 2017;Myin-Germeys & van Os, 2007;Upthegrove et al, 2017Upthegrove et al, , 2020van Nierop et al, 2018). Present findings suggest a particularly strong association between depression and hallucinatory experiences in the network of women compared to men, corroborating the idea that such an affective pathway to psychosis involving depression may be expressed to a greater degree in women, potentially funneled by increased emotional reactivity to life events and daily hassles (Davis et al, 1999;Hodes & Epperson, 2019;Myin-Germeys & van Os, 2007;Stainton et al, 2021).…”
Section: Differences In Symptom Network Of Women and Menmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 13, 2021. ; https://doi.org/10.1101/2021.05.06.21256748 doi: medRxiv preprint Thus far, however, heterogeneity in symptom networks of psychosis has been either overlooked or addressed in a partial way on a single candidate risk factor (such as sex, cannabis use or socioeconomic background) at specific thresholds, or using summed environmental risk scores (Betz et al, 2020;Guloksuz et al, 2016;Isvoranu et al, 2016;Wüsten et al, 2018), which lose specificity and relevance for real work prevention and intervention.…”
Section: Introductionmentioning
confidence: 99%